Screening and Isolation of H2S Decrease Microba for Biogas Purification from POME On Biogas Power Plant - agustina dyah setyowati; Joni Prasetyo (Program Studi Teknik Kimia, Universitas Pamulang, 2020)
Biogas is a renewable alternative energy that can be produced from POME (Palm Oil Mill Effluent). Biogas consists of Methane (CH4), Carbon Dioxide (CO2) and a small amount of Hydrogen Sulfide (H2S) while Nitrogen (N2) and Oxygen (O2) are usually from the remaining air composition analyzed in the sample. In biogas, Hydrogen Sulfide consists more than 1200 ppm can cause corrosive so it is often a problem in the surrounding environment because it can damage equipments. A way to reducing H2S is by microbiological processes using microorganisms such as Thiobacillus. Thiobacillus is a chemototrophic bacteria that is able to decompose toxic into non-toxic chemical compounds. This research was carried out in several stages, namely: microbial screening process gas of H2S, isolation of potential microbial media containing sulfur NaHS, data analyst using Sulfur Analyzer. The process of isolation and screening of Indonesian microbes (indigeneous) uses conventional isolation methods, namely isolation using the process level with isolation stage: the first stage is sampling from nature, the second stage of dilution of samples in sterile water, the third stage of storage for agar media, the fourth stage of mixing in samples of petri dishes, the fifth stage of incubation and the last stage of examination of incubation results.While for microbial separation using the agar scraping method.